Failure of High-Dose Daptomycin for Bacteremia Caused by Daptomycin-Susceptible Enterococcus faecium Harboring LiaSR Substitutions (2014)
High-dose daptomycin (DAP) therapy failed in a neutropenic patient with bloodstream infection caused by a DAP-susceptible Enterococcus faecium (minimum inhibitory concentration, 3 μg/mL) harboring genetic changes associated with DAP resistance, with persistent bacteremia and selection of additional resistances. Daptomycin monotherapy should be used cautiously against DAP-susceptible E. faecium strains with minimum inhibitory concentrations >2 μg/mL.